Traditional and 3D Stem Cell Cultures Maintained in Xenobiotic-Free Conditions: Immunological Aspects - Sakalem, Marna E. [UNESP]; Brand, Heloisa; dos Santos, Natália C.D.; de Oliveira, Rafael G. [UNESP] (Elsevier, 2024)
The possibility of cultivating multiple types of cells in vitro has been a turning point in life sciences and crucial for medical advances. Either as a monolayer (bidimensional, 2D cultures) or three-dimensional (3D), the cultivation of cells on a dish enables them to mimic multiple cellular characteristics and to understand cellular processes. Also, some tissue, organ, and system processes can be replicated in a similar way to what happens in vivo. In order to successfully separate cells and keep cultures alive, several different components are necessary, and some of them are derived from animals and other species. With the possibility of cell therapy and even transplantation of cells cultivated in vitro to demanding patients, the use of supplements that derive from species different from the ones of the cultured cells—the so-called xenobiotic compounds—can trigger immunological responses in the host and increase the risk of contamination by pathogens. The present chapter aims to show an updated review of the possibilities of cell cultures using xenobiotic-free supplements, and a comparison to regular cultivation, containing non-xeno compounds. We sincerely expect, with this brief chapter, to enlighten the reader about the potential harm of unlimited xeno-compound use and to raise awareness about xeno-free alternatives that could deliver remarkably comparable results in the vast—and expanding—cell culture field.
Keywords: Allergy; Bioreactor; Cell cultivation; Immunity; Large-scale; Organoids; Spheroids; Stem cells; Xeno-free conditions; Xenobiotic compounds; Xenobiotics